Mesenchymal Stromal Cells Disrupt mTOR-Signaling and Aerobic Glycolysis During T-Cell Activation - Böttcher, Martin; Hofmann, Andreas D.; Bruns, Heiko; Haibach, Martina; Loschinski, Romy; Saul, Domenica; Mackensen, Andreas; Le Blanc, Katarina; Jitschin, Regina; Mougiakakos, Dimitrios (Stem Cells, 2016)
Mesenchymal stromal cells (MSCs) possess numerous regenerative and immune modulating functions. Transplantation across histocompatibility barriers is feasible due to their hypo-immunogenicity. MSCs have emerged as promising tools for treating graft-versus-host disease following allogeneic stem cell transplantation. It is well established that their clinical efficacy is substantially attributed to fine-tuning of T-cell responses. At the same time, increasing evidence suggests that metabolic processes control T-cell function and fate. Here, we investigated the MSCs' impact on the metabolic framework of activated T-cells. In fact, MSCs led to mitigated mTOR signaling. This phenomenon was accompanied by a weaker glycolytic response (including glucose uptake, glycolytic rate, and upregulation of glycolytic machinery) toward T-cell activating stimuli. Notably, MSCs express indoleamine-2,3-dioxygenase (IDO), which mediates T-cell suppressive tryptophan catabolism. Our observations suggest that IDO-induced tryptophan depletion interferes with a tryptophan-sufficiency signal that promotes cellular mTOR activation. Despite an immediate suppression of T-cell responses, MSCs foster a metabolically quiescent T-cell phenotype characterized by reduced mTOR signaling and glycolysis, increased autophagy, and lower oxidative stress levels. In fact, those features have previously been shown to promote generation of long-lived memory cells and it remains to be elucidated how MSC-induced metabolic effects shape in vivo T-cell immunity. Stem Cells 2016;34:516-52
EVALuna2:25707